ESTIMATING IRRIGATION WATER USE FOR DATE PALM USING REMOTE SENSING OVER AN OASIS IN ARID REGION - Biro, K.; Zeineldin, F.; Al-Hajhoj, M. R.; Dinar, H. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Date palm needs sufficient water of acceptable quality to reach its potential yield. The present study conducted in Al-Hassa Oasis located in the Eastern Region of the Kingdom of Saudi Arabia aiming to estimate the daily, monthly and annual actual evapotranspiration (ETa) for date palm using Landsat-8 satellite data during 2017/2018. Also, an attempted was made to compare between the computed ETa and the actual water applied in the field. The Surface Energy Balance Algorithm for Land (SEBAL) supported by climate data was used to calculate the ETa. The SEBAL model outputs were validated using the FAO Penman-Monteith method coupled with field observation and measurements. The results showed that the highest daily ETa value observed during the summer season was 9 mm.day−1, and the lowest value was 2 mm.day−1 in winter. The mean monthly water applied in the farms was 15% higher than that suggested by SEBAL during the peak summertime. The annual ETa varied between 800 and 1,400 mm.year−1, while the annual irrigation requirement for date palm was in the range of 11000 – 13000 m3.ha−1. The validation measure showed a significant agreement level between the SEBAL model and the FAO Penman-Monteith method with RMSE of 0.84 mm.day−1. The study concludes that the ETa calculated from the satellite data and the SEBAL model is useful for guiding the daily operation of date palm water management at the farm scale. Also, this information is essential for water planners and policymakers to formulate strategies and make decisions for managing water resources over large agricultural areas.